MANAJEMEN LABA PADA PERUSAHAAN DENGAN KELUARGA SEBAGAI PEMILIK ULTIMAT - Eni Indriani; Yusli Mariadi; Robith Hudaya (Jurnal Riset Akuntansi, 2016)
The objective of this study is to determine the influence of family ownership on the earnings management with leverage and firm size as control variables. This study focused on manufacturing companies which has family as the ultimate owner of the company. The sample of this stuacturing companies listed in the Indonesia Stock Exchange and published its annual report during 2008-2014 period. The findings of this research indicated that family ownership has influence on the behavior of earnings management in companies with family as ultimate owner, which means that the percentage of shares owned by the family affect the magnitude of earnings management conducted by the company. The results also show that leverage has no effect on the behavior of earnings management in companies with family as ultimate owner, meaning the financing ratio that comes from the ratio of debt to equity can not affect the magnitude of earnings management conducted by the company. Lastly, company Size was found to have influence on earnings management behavior, which means that the size of firm can affect the the magnitude of earnings management conducted by the company. Keywords: earnings management, family ownership, leverage, company size